Psychological impact of polygamous marriage on women and children: a systematic review and meta-analysis - Ismail Shaiful Bahari; Mohd Noor Norhayati; Nik Hussain Nik Hazlina; Che Abd Aziz Mohamad Shahirul Aiman; Nik Ahmad Nik Muhammad Arif (BMC, 2021)
Abstract Background Over the last two decades, there has been significant growth in public, political, and academic awareness of polygamy. Polygamous families have distinct household problems, usually stemming from jealousy between co-wives over the husband's affections and resources. This study aimed to ascertain the psychological impact of polygamous marriage on women and children worldwide. Methods A systematic search was performed in MEDLINE (PubMed), Scopus, CINAHL (EBSCOhost), Google Scholar, and ProQuest using search terms such as "marriage" and "polygamy." Studies published from the inception of the respective databases until April 2021 were retrieved to assess their eligibility for inclusion in this study. The Joanna Briggs Institute Critical Appraisal Checklist was used for data extraction and the quality assessment of the included studies. The generic inverse variance and odds ratios with 95% confidence intervals (CI) were calculated using RevMan software. Results There were 24 studies fulfilling the eligibility criteria, and 23 studies had a low risk of bias. The pooled meta-analysis showed women in polygamous marriages had a 2.25 (95% CI: 1.20, 4.20) higher chance of experiencing depression than in monogamous marriages. Children with polygamous parents had a significantly higher Global Severity Index with a mean difference of 0.21 (95% CI: 0.10, 0.33) than those with monogamous parents. Conclusions The psychological impact of polygamous marriage on women and children was found to be relatively higher than monogamous marriage. Awareness of the proper practices for polygamy should be strengthened so that its adverse effects can be minimized. The agencies involved in polygamous practices should broaden and enhance their understanding of the correct practice of polygamy.